2000
DOI: 10.1207/s15327906mbr3504_03
|View full text |Cite
|
Sign up to set email alerts
|

Linear Confirmatory Factor Models to Evaluate Multitrait-Multimethod Matrices: The Effects of Number of Indicators and Correlation Among Methods

Abstract: Two models for confirmatory factor analysis of multitrait-multimethod data (MTMM) were assessed, the correlated traits-correlated methods (CTCM), and the correlated traits-correlated uniqueness models (CTCU). Two Monte Carlo experiments (100 replications per cell) were performed to study the behavior of these models in terms of magnitude and direction of bias, and accuracy of estimates. Study one included a single indicator per trait-method combination, and it manipulated three independent variables: matrix ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…However, they found evidence of only small positive biases in the CU model (.02 and .047 on average for trait loadings and trait correlations, respectively) and concluded that those biases were trivial. A second simula-tion study found similarly small bias (Tomás, Hontangas, & Oliver, 2000 Despite these findings, we still believe there is the potential for substantial bias in trait estimates under the CU model, especially when there is substantial method variance shared between variables. Tomás et al (2000) were correct to point out the importance of method correlations, but Equations 1a and 1b show that what is really critical is the product of a method correlation and two method factor loadings.…”
Section: Potential Bias In Estimated Trait-related Parameters Under Tmentioning
confidence: 77%
See 3 more Smart Citations
“…However, they found evidence of only small positive biases in the CU model (.02 and .047 on average for trait loadings and trait correlations, respectively) and concluded that those biases were trivial. A second simula-tion study found similarly small bias (Tomás, Hontangas, & Oliver, 2000 Despite these findings, we still believe there is the potential for substantial bias in trait estimates under the CU model, especially when there is substantial method variance shared between variables. Tomás et al (2000) were correct to point out the importance of method correlations, but Equations 1a and 1b show that what is really critical is the product of a method correlation and two method factor loadings.…”
Section: Potential Bias In Estimated Trait-related Parameters Under Tmentioning
confidence: 77%
“…A second simula-tion study found similarly small bias (Tomás, Hontangas, & Oliver, 2000 Despite these findings, we still believe there is the potential for substantial bias in trait estimates under the CU model, especially when there is substantial method variance shared between variables. Tomás et al (2000) were correct to point out the importance of method correlations, but Equations 1a and 1b show that what is really critical is the product of a method correlation and two method factor loadings. For example, if two methods are highly correlated, but a pair of variables each has a low loading on its measurement method factor, then the correlation between those two variables will not be inflated much (there is little common method bias).…”
Section: Potential Bias In Estimated Trait-related Parameters Under Tmentioning
confidence: 77%
See 2 more Smart Citations
“…The population model used for this study includes three latent variables, an equal number of items per latent variable, and no cross-loadings. This model was selected for its simplicity and similarity to population models employed by previous research (e.g., Henseler, 2012;Hwang, Malhotra, et al, 2010;Paxton, Curran, bollen, Kirby, & Chen, 2001;Tomás, Hontangas, Oliver, 2000). The population model used for conditions featuring reflective indicator-latent variable relationships is identical to model used by Hwang, Malhotra, et al (2010) and Paxton et al (2001), and is displayed in Figure 1.…”
Section: Simulation Designmentioning
confidence: 99%